(untitled) (Research, Society and Development, 2020)
Objective: To evaluate the amplitude and pattern of mouth opening in patients diagnosed with Temporomandibular Disorder (TMD) who underwent treatment with Occlusal Plaque (PO) and Physiotherapy (F) after 1 and 3 months of treatment. Methodology: The mouth opening pattern and the mouth opening amplitude of 48 patients submitted to a randomized clinical trial and divided into 2 treatment groups were evaluated: occlusal plaque (PO; N = 23) and physical therapy (F; N = 25) . All patients were diagnosed with TMD according to axis 1 of the RDC / TMD (Research Diagnostic Criteria for Temporomandibular Disorders). The collected data were evaluated using the SPSS program using the Wilcoxon, Kruskal Wallis and Fisher’s exact Chi Square tests. Results: PO and F showed similar performance in the opening pattern, maintaining the same pattern as the patient over the treatment time (P = 0.003). At the maximum opening amplitude without assistance, both therapies showed a significant improvement in amplitude gain in the initial time and after one month of therapy (P = 0.002), maintaining the amplitude until the third month, without presenting significant gain. Conclusion: PO and F showed similar performance for the treatment of TMD when analyzing the opening pattern and the mean maximum opening amplitude without assistance.